La yuca para alimentacion animal - Reeves, J. (1987)
The importance of cassava, particularly in animal nutrition, is briefly discussed. The adaptability of cassava to infertile soils and low inputs, its production of more calories per land and labor unit than any other food crop, and its resistance to pests and diseases are highlighted. CIAT`s objectives in Latin America and Colombia are presented. (CIAT)